Understanding of Requirements Engineering using The Three Dimensions of Requirements Engineering Method in Platform Development - Sari, Risna; Anggi Muhammad Rifa'i; Muhammad Salimy Ahsan; M Ilham Arief; Mohammad Rezza Pahlevi (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
Requirements engineering is a critical activity in a development system project, the increasing need for complexity of software development and the heterogeneity of stakeholders in motivating the development of methods and the need to evaluate the engineering requirements needed and aim to lead to a large scale. This study presents a paper in an empirical form that aims to identify and understand the characteristics of the advantages and limitations of the developed platform so that we can know the challenges that will be faced, such as expectations and input from experts for the development of the platform that we develop so that it can be in accordance with what users expect. We conducted this research with the aim of understanding the engineering requirements in the research we developed by utilizing the three dimensions of the requirements engineering method, which consists of requirement elicitation, requirement specification, and requirement validation and verification. The research we conducted managed to understand the stages of needs engineering by producing many documents that help the platform development process. We get the most important UI value from attractiveness, clarity, efficiency, accuracy, stimulation, and novelty, which is 63.2% with a very interest rating, 55.6 with a very interest rating, 57.9% with a very interest rating, 44.4% with a balanced rating between interesting and very interest, 52.6% with an interesting rating, 42.1% with a very interesting rating. We get product values consisting of attractiveness, clarity, efficiency, accuracy, stimulation, and novelty, namely 68.4% with a very interest rating, 52.6% with an interest ng rating, 52.6% with a very interest rating, 47.4% with a balanced rating between interesting and very interest, 47.4% with a balanced rating between interesting and very interest, 47.4% with a balanced rating between interesting and very interest